Sales and distribution networks of Fast Moving Consumer Goods (FMCGS) companies in Ghana. A case study of selected companies in the Kumasi Metropolis. - Leroy, Kwadwo Darkwah Junior (2017)
A thesis submitted to the Department of Marketing and Corporate Strategy, Kwame Nkrumah University of Science and Technology in partial fulfillment of the award of the degree of Master of Business Administration (Marketing -Option) KNUST School of Business College of Humanities and Social Sciences,